Health Operational Assistance Funds : Literature Review - Retno Prihastuti; Ascobat Gani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: BOK funds are primarily intended for services at Puskesmas, reducing maternal mortality, reducing infant mortality and addressing malnutrition. The existence of BOK funds at Puskesmas is expected to have an impact on improving service coverage and programme effectiveness. However, the absorption of BOK funds is considered not optimal. Objective: This study aims to determine the factors that influence the implementation and absorption of BOK funds. Method: The research method is literature review by using the search engines Google Scholar, Crossref and Garuda Portal from 2014 to 2023. The papers to be reviewed were selected based on inclusion and exclusion criteria. 13 studies were found that fulfilled the criteria. Result: Delays in the disbursement of funds are an obstacle in the management of BOK which results in inefficiency and non-achievement of set targets. Limited human resources at Puskesmas and high workload or overlapping tasks are also an obstacle at Puskesmas including in the management of BOK. Competent human resources are needed in the management of BOK funds. Conclusion: Delays in fund disbursement and limited human resources hamper BOK management.